ISSR-based genetic diversity of wild and ex situ conserved population of Hopea chinensis (Merr.) Hand.-Mazz (Bangladesh Journal of Botany, 2018)
The genetic diversity and structure of 4 wild population and 2 ex situ conserved population of Hopea chinensis (Merr.) Hand.-Mazz were analyzed and compared by ISSR marker method. Fifty eight bands were amplified from total genomic DNA with 10 primers in which there were 51 polymorphic, the percentage of polymorphic bands of populations ranged from 53.45 to 79.31, with an average value of 69.82, indicating the presence of high genetic diversity. However, the percentage of polymorphic band, Nei’s diversity index (He) and Shannon information index (I) of wild populations (86.21, 0.3636 and 0.5232, respectively) were higher than those of ex situ conservated populations (77.59, 0.3153 and 0.4597, respectively), which meant that ex situ conservations of Hopea chinensis had a narrow genetic diversity. Population structure analysis revealed that genetic variation of Hopea chinensis was 0.0373, so the genetic differentiation was 3.73% among populations, and 96.27% in populations. Furthermore, the strong gene flow (Nm = 12.8896) would be the main reason of limited population differentiation. It concluded that ex situ population had not yet fully covered the entire genetic diversity of Hopea chinensis.